Directory of Schemes for Voluntary Agencies - Planning Commission (Planning Commission, 1994)
Selection of the nodal agency would be through an open and transparent system of advertisement in the leading newspapers, shortlisting through an empowered committee on objective grading made on the basis of data furnished and final selection would be made by the State AIDS Committee. Under exceptional circumstances, like in North Eastern State and smaller States or Union Territories, NACO can do this exercise for the entire region or part of it.
Voluntary Action Coordination Cell Planning Commission
Voluntary Action Coordination Cell Planning Commission